Bisabololoxide A, One of the Constituents in German Chamomile Extract, Attenuates Cell Death Induced by Calcium Overload. (19th July 2013) - Fukunaga, Eri; Hirao, Yumi; Ogata‐Ikeda, Ikuko; Nishimura, Yumiko; Seo, Hakaru; Oyama, Yasuo
<x xml:space="preserve">Abstract</x> Bisabololoxide A (BSBO), main constituents in German chamomile extract, is responsible for antipruritic effect. In previous study, the incubation with 30–100 μM BSBO for 24 h exerted cytotoxic and proapoptotic effects on rat thymocytes. To further characterize BSBO cytotoxicity, the effect on the cells suffering from calcium overload by calcium ionophore A23187 was examined. A23187 induced Ca2+‐dependent cell death. Contrary to our expectation, 1–10 μM BSBO inhibited A23187‐induced increase in cell lethality of rat thymocytes. BSBO attenuated A23187‐induced increases in populations of shrunken living cells, phosphatidylserine‐exposed living cells, and dead cells, without affecting the increase in intracellular Ca2+ concentration and the Ca2+‐dependent hyperpolarization. The effect of BSBO on A23187‐treated cells may be unique because the activation of Ca2+‐dependent K+ channels is required for cell shrinkage, externalization of phosphatidylserine, and cell death in some cells. The cell death induced by A23187 was not inhibited by Z‐VAD‐FMK, a pan‐inhibitor of caspases. Thus, the cell death may be a necrosis with some features observed during an early stage of apoptosis. These results suggest that BSBO at low micromolar concentrations is cytoprotective against calcium overload. Copyright © 2013 John Wiley & Sons, Ltd.